PEMBERIAN REWARD TERHADAP MINAT DAN HASIL BELAJAR IPS KELAS IX SMPN 2 SUMBERGEMPOL - Safitri, Erika Ainun; Putranto, Anggoro (Jurnal Kajian Pembelajaran dan Keilmuan, 2023)
The research conducted aims: (1) Determine the effect of giving rewards on the interest in learning social studies class IX SMPN 2 Sumbergempol. (2) Knowing the effect of giving rewards on the learning outcomes of social studies class IX SMPN 2 Sumbergempol. The research method is quasi experiment design with a quantitative approach. Pada penelitian populasi berupa siswa kelas IX SMPN 2 Sumbergempol. Data were collected by questionnaires and posttests conducted in experimental and control classes. Data analysis using the SPSS 25 application is in the form of prerequisite tests in the form of normality and homogeneity tests, while hypothesis tests are in the form of t-tests. Results obtained from the study: (1) There is a significant influence on the interest in learning social studies class IX SMPN 2 Sumbergempol. This is seen in Sig. 0.045 0.05. Giving rewards has a significant influence on interest in learning. (2) There is a significant influence on the provision of rewards on the learning outcomes of social studies class IX SMPN 2 Sumbergempol. This is seen in Sig. 0.000 0.05. Rewarding has a significant effect on learning outcomes.